2020
DOI: 10.1590/1678-992x-2018-0224
|View full text |Cite
|
Sign up to set email alerts
|

Sample size and prediction of weight and yield of individual cuts from Braford steers pistol hindquarters

Abstract: Two hundred seventeen grass-finished Braford steers were assessed by ultrasonic scanning and subsequently harvested with their pistol hindquarters fabricated into boneless wholesale cuts. The Longissimus thoracis muscle area and subcutaneous fat depths were measured. The objectives of this study were: 1) to develop prediction equations for weights of the pistol hindquarter and high-value commercial cuts, and 2) to estimate sample size needed for experiments comparing pistol hindquarter retail product weight us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The measurements in the live animal did not result in substantial increases in R² but led to reducing the lack of fit (Cp~p) and reduced residual variance (Cardoso et al, 2020). Hernandez-Espinoza et al (2012) reported that carcass yield is associated with withers height.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements in the live animal did not result in substantial increases in R² but led to reducing the lack of fit (Cp~p) and reduced residual variance (Cardoso et al, 2020). Hernandez-Espinoza et al (2012) reported that carcass yield is associated with withers height.…”
Section: Discussionmentioning
confidence: 99%
“… Pabiou et al (2011) proposed such a strategy using video image analysis of cattle carcasses and reported a correlation of up to 0.96 between groups of primal carcass yields (i.e., very high-value cuts, high-value cuts, medium value cuts, and low value cuts) and the respective yield predictions from video image analyses. Using a population of 217 commercial Bradford Brazilian steers, Cardoso et al (2019) documented the ability of ultrasound measures of longissimus thoracic muscle area and/or subcutaneous fat thickness on live animals immediately prior to slaughter to predict pistol hindquarter cut weights. Other technologies to predict carcass characteristics also exist, each with differing levels of prediction accuracy and cost ( Scholz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Body measurements of BL, and FG and TG in cattle are important, since these measurements correlate positively with carcasses of greater size, better conformation (Pacheco et al, 2014), and greater retail cut yield (Pascoal et al, 2010;Cardoso et al, 2020). The selection of animals with greater muscling adds value at slaughter, as their carcasses have greater dressing percentages and yields of retail cuts (Cardoso et al, 2020).…”
Section: Effects Of Genetic Groups Within Mating Systems (Purebred and Crossbred)mentioning
confidence: 99%